Evoluç\~ao de índices de tecnologia do complexo metalomecânico no Brasil: 1985-2009 - Luiz Dias Bahia; Bruno Rodrigues Pinheiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper seeks to quantify the technological evolution of production in the mechanical sectors of the Brazilian Industry since 1985 until 2009. The main conclusion is the following: it have been a generalized augmentation of productive efficiency and more localized experiences of secondary innovation.
Keywords: D2; D61; 330; Brazilian industry; technology; efficiency